Acute and longitudinal effects of weighted vest training on sprint-running performance: a systematic review - Macadam, P.; Cronin, J. B.; Feser, E. H. (Sports Biomechanics, 2022)
This systematic review aimed to quantify the acute and longitudinal effects that occur with weighted vests during sprint-running. PubMed, SPORTDiscus, and Web of Science were searched using the Boolean phrases (vest OR trunk) AND (sprint*) AND (resist* OR weight OR load*). From 170 articles retrieved, 11 studies (6 acute, 5 longitudinal) met the inclusion criteria. Vest loads (5-40% body mass) were found to significantly increase acute over-ground times (10-50 m 4.1-16.9%, effect sizes [ES] = 0.93-3.11) through significantly decreased velocity (-2.2% to -17.3%, ES = -0.41 to -3.19), horizontal force (-5.9% to -22.1%, ES = -0.85 to -3.30), maximal power (-4.3% to -35.6%, ES = -0.32 to -3.44), and flight times (-8.3% to -14.6%, ES = -0.88 to -1.03), while increasing contact times (14.7-19.6%, ES = 1.80-3.17). Treadmill sprints were less effected until loads >11% body mass were used. Improvements in velocity (1.2-1.3%, ES = 0.24-0.37) and times (10-50 m 1.2-9.4%, ES = 0.25-3.30) were found in longitudinal studies (5.6-18.9% body mass, 3-7 weeks). Future studies should focus on determining the optimum load and volume to clearly establish the training benefits of this form of resisted sprinting.